Analisis Penerbitan Sukuk Negara Ritel Seri-015 tahun 2021 - Nurman Ferdiana; Muhammad Iqbal Fasa; A. Kumedi Ja’far (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
In the world of Indonesian state finance, there are many types and varieties of financial products in circulation. As a society with the 4th largest population in the world, Indonesia is a very lucrative market share. This is often the main discussion in international organizations where Indonesia as a developing country is heading to a developed country. One product that is in great demand from year to year is retail sukuk. There are 15 Retail Sukuk products called Retail Sukuk 015. The products offered by the Indonesian government are very profitable on a certain scale. Where Retail Sukuk (retail sukuk) are a Sharia investment product offered by the government to individual Indonesian citizens. The management presented by Retail Sukuk must be based on Sharia principles, avoiding the elements of maysir (gambling), gharar (obscurity) and no usury (usury). The concept offered has also received a guarantee from the DSN MUI so that the contract used to issue Retail Sukuk is Ijarah-Asset to be leased. The existing capital turnover was developed for investment activities to purchase benefit rights to State Property leased by the government to procurement projects (project businesses). So the rewards are clearly taken or shared from the profits from the investment activities. To add to the clarity of how these benefits are obtained, it is described through 8 (eight) investment benefits issued by the Ministry of Finance as an extension of the Indonesian government. Therefore, the Government has a definite goal where the issuance of retail sukuk is to help finance the APBN and finance the development of various infrastructures in Indonesia. Keywords: Retail Sukuk, Sharia, Investment